Interactive Augmented Reality (IAR)-Based Student Worksheets (LKPD): A Solution & Variation of Abstract Learning Media to Concrete in Middle School - Maulisa Irdania; Ervan Johan Wicaksana; Desfaur Natalia (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
This study aimed to develop a Student Worksheet (LKPD) on the human digestive system material integrated with Interactive Augmented Reality (IAR) using Android and to evaluate its feasibility based on expert, teacher, and student assessments. The research employed a Research and Development (R&D) approach with the 4D model consisting of Define, Design, Develop, and Disseminate stages. Data were collected through validation questionnaires from material and media experts and assessment questionnaires from science teachers and students. The trial subjects were Grade VIII students at SMP Muhammadiyah Kuala Tungkal. Material expert validation was carried out in three stages, resulting in a 100% score, categorized as “Very Feasible.” Media expert validation, conducted in two phases, obtained a score of 95%, also categorized as “Very Feasible.” Science teacher assessment yielded 85% (“Very Eligible”), while student assessments showed 81% in the small group trial and 84% in the large group trial, both categorized as “Very Eligible”. The findings indicate that the developed LKPD, supported by Interactive Augmented Reality technology on Android, meets the feasibility standards for use as a learning medium and teaching material for Grade VIII junior high school students in the human digestive system topic. This integration of IAR is expected to enhance learning interactivity, student engagement, and conceptual understanding in science education.